Food And Beverage Marketing Strategy With Digital Media Influencer At Sentrum Space D.I.Yogyakarta: English - Hafidz Dhiya Fawwaz; Sumadi Sumadi (International Journal of Economics, Business and Innovation Research, 2024)
This research is a report on an internship carried out by the author for 4 months at the Sentrum Space company, with a focus on the marketing division. The method used is a qualitative approach with data collection techniques through in-depth observation, participation as an intern, and documentation studies. The research aims to examine the influence of influencers in marketing Sentrum Space. SWOT analysis shows that the company's main strength is digital-based promotion and optimal use of Instagram features, while its weakness lies in the low quantity of human resources. The opportunity to be exploited is the development of digital technology and low brand awareness, while the threat is competition and lack of company recognition. The marketing strategy is based on SWOT analysis, with a focus on optimizing the use of digital platforms, improving service quality, and utilizing social media as a marketing tool. Thus, this research provides insight into Sentrum Space's digital marketing strategy and recommendations for increasing the company's marketing success through digital platforms.